2018
DOI: 10.1016/j.janxdis.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Insula activation is modulated by attention shifting in social anxiety disorder

Abstract: Social anxiety disorder (SAD) is characterized by exaggerated reactivity to social threat, often documented by biased attention to threatening information, and increased activation in brain regions involved in salience/threat processing. Attention training has been developed to ameliorate the attention bias documented in individuals with SAD, with mixed results. We investigated patterns of brain activation underlying acute attention modulation in 41 participants (29 with SAD and 12 health controls). We then in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…High rates of anxiety and depression symptoms have been found in PE patients (Mourikis et al, 2015). Previous neuroimaging studies demonstrated that the brain networks for attention and emotion regulation were disrupted in patients with anxiety disorders (Duval et al, 2018;Greenberg et al, 2017;Pic o-Pérez et al, 2017;Tan et al, 2018). The prefrontal cortex, especially inferior medial prefrontal cortex, have been identified as a core area for attention and emotion processing (Doll et al, 2016;Geday & Gjedde, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…High rates of anxiety and depression symptoms have been found in PE patients (Mourikis et al, 2015). Previous neuroimaging studies demonstrated that the brain networks for attention and emotion regulation were disrupted in patients with anxiety disorders (Duval et al, 2018;Greenberg et al, 2017;Pic o-Pérez et al, 2017;Tan et al, 2018). The prefrontal cortex, especially inferior medial prefrontal cortex, have been identified as a core area for attention and emotion processing (Doll et al, 2016;Geday & Gjedde, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For data sets that include repeated visits (i.e., ABCD, UKBiobank), only the first visit was included. Other included data come from studies conducted at the University of Michigan (Duval et al, 2018;Rutherford et al, 2020;Tomlinson et al, 2020;Tso et al, 2021;Weigard et al, 2021;Zucker et al, 1996), University of California Davis (Nordahl et al, 2020), University of Oslo (Nesvåg et al, 2017), King's College London (Green et al, 2012;Lythe et al, 2015), and Amsterdam University Medical Center (Mocking et al, 2016). Full details regarding sample characteristics, diagnostic procedures and acquisition protocols can be found in the publications associated with each of the studies.…”
Section: Methodsmentioning
confidence: 99%
“…The middle insula is suggested to be associated with polymodal integration and may also play an important role in motor processes and regulation. The posterior insula is proposed to be associated with interoceptive processes and awareness of the bodily state, as well as potential in attention, sensory, and social processes (Di Cesare, Pinardi, et al, 2018;Duval, Joshi, Russman Block, Abelson, & Liberzon, 2018;Schiff et al, 2018;Wang et al, 2018;Zhang et al, 2019). It is of note that most differences, even those not reaching significance, were found in the left hemisphere.…”
Section: Discussionmentioning
confidence: 99%